Saúde digital no meio ambiente do trabalho - Ribeiro, Adriano Cezar (2024)
This research seeks to contextualize workers' right to digital health. In this area, discussions range from the genesis of man as a modifier of the environment in which he is inserted to hypotheses of the working environment in the metaverse, demonstrating the creation, development and trends that involve the construction of the worker's right to a healthy quality of life in the environment. digital/virtual environment. Parameters are created in this discourse of hyper connectivity and digital dependence that we are part of in our daily lives, as building activities of any nature without dependence on the internet, a smartphone or social networks is an almost impossible configuration to think about in any activity that involves propose to do it today. This context involves teleworking, home office, home work or immersive virtual environment (metaverse); The worker involved in these aspects has inherent rights to health. Digital health in this research does not mean the manifestation or form of the application of medicine in distance treatments through sensing and personal interaction technologies, but rather the right to balanced health, a healthy quality of life, the right to disconnection, the minimum vital level and conditions of predictability and precaution in the chances of avoiding occupational diseases, all with the aim of guaranteeing the healthy development of work in the digital/virtual work environment. The research method applied is qualitative exploratory research, seeking to understand the topic in its general aspect, based on bibliographic analysis and observations taken from books, scientific articles, doctoral theses, laws, doctrines, jurisprudence and internet research, in addition to analyzing lectures, podcasts and films, until we obtain the necessary filter to approach specific points. The general objective is to understand the worker's right to digital health in their work environment, with specific objectives being the understanding of the genesis of the work environment, the temporal development through the industrial revolutions until the formatting of the digital/virtual environment and a proposal on workers’ right to digital health. We lack works that address this topic in its entirety, which is why it is necessary to go a little further than traditional research and grammatical interpretation, making it necessary to create options for scenarios that can be used and confronted with the possibilities already experienced and already consolidated data. In this case, hypothetical-deductive situations are used, starting from the general to reach the specific points proposed. The law must accompany social evolution as quickly as it happens, this work is a grain in the construction of this cutting-edge subject, demonstrating the need for its regulations, so that technology can be an ally factor in the development and aggrandizement of us all.